Desenvolvimento de equipamento para medida de pressão arterial batimento a batimento comparado com a pressão arterial invasiva durante procedimentos de angiocoronariografia - Borges, Melania Aparecida [UNIFESP] (2018)
Developing and testing a blood pressure beattobeat monitoring device during coronary angiography and subsequently compare with the measurements obtained from invasive blood pressure. Methods: Twentyeight patients with an indication of hemodynamic study were included and remained in the horizontal dorsal decubitus position. Before onset coronary angiography they were guided about the use of the left radial bracelet to monitor blood pressure. Results: There was a significant difference between the time required for the hemodynamic team to acquire the first measurement of invasive blood pressure and the time of the first measurement of heart beat (11.1 ± 5.1 and 1.5 ± 1.8 p <0.0001, respectively). The intraclass correlation coefficients (95% CI) of systolic and diastolic blood pressure were 0.897 (0.780 0.952) and 0.876 (0.734 0.942), respectively, indicating good reproducibility. Conclusion: this study showed the process of developing an equipment to evaluate beattobeat blood pressure but when compared to invasive blood pressure there were no significant differences between the two measurements. This technique may be a promising coadjuvant tool associated with invasive monitoring during coronary angiography procedures.